On the Trail of Paediatric Liver Transplant in South Africa: Social Challenges to Equitable Distribution in Organ Transplantation - Sideris, Tina C.; Fabian, June (Health Tomorrow: Interdisciplinarity and Internationality, 2015)
This paper tracks the journey of a family from a remote rural area in South Africa – a 2 year old child born with a life threatening liver disease, and his unemployed mother – who, by a series of contingencies, are sent on the trail of organ transplantation to land at the door of a private organ transplant centre. This case brings into focus the dilemmas that social factors present for equitable distribution of organ transplantation. The paper focuses on two interconnected issues: the link between socio-economic status and access to treatment, and existing practices of rationing. The uncritical conjunction of socio-economic status and organ transplantation disadvantages vulnerable sectors of the population. Yet, social circumstances impact the management of specialized medical treatment, which in itself imposes burdens on those with limited resources. Similarly, although this paper poses questions about indiscriminate practices, it accepts the inevitable rationing of health care.